Applications of parallel processing in vision - Brannan, Julie R., 1962- (Advances in psychology (Amsterdam, Netherlands), 1992)
Considerable evidence exists that visual sensory information is analyzed simultaneously along two or more independent pathways. In the past two decades, researchers have extensively used the concept of parallel visual channels as a framework to direct their explorations of human vision. More recently, basic and clinical scientists have found such a dichotomy applicable to the way we organize our knowledge of visual development, higher order perception, and visual disorders, to name just a few. This volume attempts to provide a forum for gathering these different perspectives.